Affordances in the home environment of children at risk of developmental delay - Janaína Araujo Teixeira Santos; Amanda Larissa Oliveira Lima; Letícia Dias dos Santos Silva; Fernanda da Costa Braga; Marcelo Machado Alécio; Paula Silva de Carvalho Chagas; Érica Cesário Defilipo; Aline Martins de Toledo; Paulo José Barbosa Gutierres Filho; Kênnea Martins Almeida Ayupe (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: The aim of this study was to verify the adequacy of affordances in the home environment of children at risk of developmental delay and to identify factors associated with their frequency. Methods: The cross-sectional study included 97 families who responded to the Affordances in the Home Environment for Motor Development - Infant Scale (AHEMD-IS) for 3-18 months (n=63), or AHEMD - Self-Report (AHEMD-SR) for 18-42 months (n=34). The Mann-Whitney U test was used to identify the differences between the frequencies of affordances between the groups. Multiple linear regression was used to verify the association between the child's sex, mother's marital status, education, socioeconomic level, child and mother's ages, house residents' number, per capita income, and AHEMD scores (α=0.05). Results: The home affordances' frequency in the AHEMD-IS ranged from less than adequate to excellent, while in the AHEMD-SR, the highest predominance was medium. The offer of stimuli in the AHEMD-IS was significantly higher. Higher socioeconomic level and house residents' number were associated with greater affordances. Conclusions: The higher the socioeconomic level and house residents' number, the greater the affordances in the homes of children at risk of delay. It is necessary to provide families with some alternatives to make their home environments richer in affordances that favor child development.